The role of cacao extract in reduction of the number of mutans streptococci colonies in the saliva of 12-14 year-old-children - Fajriani; Annisa Wicita Mustamin; Asmawati (Wolters Kluwer Medknow Publications, 2016)
Background: Cacao bean husk ethanol extract (CBHEE) has polyphenol that acts as an antibacterial agent, specially anti-glucosyltransferase. Aim: This study is aimed to see the effectiveness of CBHEE to reduce the number of mutans streptococci colonies in the saliva of children (with young permanent teeth), when CBHE is used as mouth rinse. Materials and Methods: This study used cross-sectional study design with time-series experimental study and used simple random sampling on 30 subjects. The chosen subjects are those who have middle oral hygiene status (OHI-S). Each subject was given the same intervention; in the first step, saliva was collected from the subjects (prior to intervention), in the second step, the subjects were given 15 mL of CBHEE 0.1% mouth rinse to rinse their mouth for about 30 s. After intervention, their saliva was collected twice in 15 min and 30 min after intervention. Furthermore, the number of mutans streptococci colonies were measured in colony-forming units (CFU) and the data was statistically analyzed using analysis of variance (ANOVA) and paired t-test. The data was analyzed and proccessed using Statistical Package for the Social Sciences (SPSS) 22.0 for windows versions. Results: The data statistically showed, significantly, the reduction of Streptococcus mutans colonies before and after 30 min of intervention. Before intervention, there were 59.10 CFU/mL of mutans streptococci, and after 15 min of intervention it showed reduction of mutans streptococci to 25.73 CFU/mL and after 30 min of intervention, the counts of mutans streptococci showed a reduction to 9.40 CFU/mL. From the test results, statistical value of this research was P = 0.000 (P < 0.05), which means that the reduction of the mutans streptococci count was significant. Conclusion: Using CBHEE as mouth rinse for children has been proven highly effective in reducing mutans streptococci colony counts in the mouth.